Facile synthesis of high surface area molybdenum carbide nanoparticles. Issue 6 (5th December 2018) - Nayak, Shanti Kiran; Benavidez, Angelica D.; Garzon, Fernando H.
Abstract: Molybdenum carbide has immense potential as an active catalyst for reaction systems such as synthesis of important chemicals like ammonia. However, the carbide is not used as a commercial catalyst or support as the current synthesis processes produce low surface area material or have contaminants such as excess carbon and surface and chemisorbed oxygen. Moreover, attempts to refine the synthesis pathways are usually not supported by any thermochemical modeling. In this study, a facile and reproducible method to synthesize high surface area molybdenum carbide was developed with the help of thermochemical modeling to better understand molybdenum‐carbon phase behavior. We have synthesized 2‐5 nm particles of Mox C with surface areas of up to 360 m 2 /g as characterized using a variety of techniques including X‐ray diffraction and electron microscopy. Abstract : Refining synthesis pathways using thermochemical modeling.